2020
DOI: 10.1038/s41598-020-77124-9
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic expression and clinical outcomes in a South Asian PRKAG2 cardiomyopathy cohort

Abstract: The PRKAG2 syndrome is a rare autosomal dominant phenocopy of sarcomeric hypertrophic cardiomyopathy (HCM), characterized by ventricular pre-excitation, progressive conduction system disease and left ventricular hypertrophy. This study describes the phenotype, genotype and clinical outcomes of a South-Asian PRKAG2 cardiomyopathy cohort over a 7-year period. Clinical, electrocardiographic, echocardiographic, and cardiac MRI data from 22 individuals with PRKAG2 variants (68% men; mean age 39.5 ± 18.1 years), ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…It is generally accepted that HCM associated with sarcomere gene mutations has a worse prognosis than non-sarcomeric forms of the disease ( Ho et al, 2018 ; Marstrand et al, 2020 ). However, several exceptions exist, such as HCM, associated with PRKAG2 gene mutations ( Ahamed et al, 2020 ). Thus, such rare clinical variants are waiting for more cases reported along with broader clinical and prospective descriptions.…”
Section: Discussionmentioning
confidence: 99%
“…It is generally accepted that HCM associated with sarcomere gene mutations has a worse prognosis than non-sarcomeric forms of the disease ( Ho et al, 2018 ; Marstrand et al, 2020 ). However, several exceptions exist, such as HCM, associated with PRKAG2 gene mutations ( Ahamed et al, 2020 ). Thus, such rare clinical variants are waiting for more cases reported along with broader clinical and prospective descriptions.…”
Section: Discussionmentioning
confidence: 99%
“…Clinically, PRKAG2 mutations cause glycogen-storage cardiomyopathy, ventricular preexcitation, and conduction system degeneration ( 15 , 16 ). Typical clinical symptoms can develop at approximately 40 years.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, a group of heterogeneous diseases with specific genetic mutations was found to have similar HCM phenotypes, such as Anderson–Fabry disease (GLA), PRKAG2 syndrome, Danon disease (LAMP2), Pompe’s disease (GAA), LEOPARD, Noonan’s syndromes (RAF1 and PTPN11), TTR (amyloidosis), and Friederich’s ataxia (FXN) [ 4 , 5 ]. However, the prevalence of these rare diseases is diverse in different regions [ 6 ]. At present, it remains a challenge to accurately identify these rare diseases among patients with phenotypic HCM.…”
Section: Introductionmentioning
confidence: 99%